Understanding IT governance for the operation of shared services in public service networks. (22nd January 2007) - Janssen, Marijn; Joha, Anton
Public organisations have started cooperating in public service networks to share services and in this way improve their service provision and simultaneously accomplish efficiency gains. The IT governance of shared services in a service network is a complicated endeavour, as it often involves multiple agencies having different objectives, resources, capabilities, processes and levels of IT sophistication. The aim of this research is to develop a better understanding of the IT governance of shared services in public service networks. Two case studies are analysed from a resource-based and a dynamic capability point of view. We found that IT governance mechanisms need to deal with the different characteristics of agencies and to balance customisation and commoditisation of services to accomplish efficiency benefits. The findings also indicate that the ability to share services in public networks and the accomplishment of the objectives of individual agencies within the network are influenced by the type of IT governance mechanisms.